Q fever and early pregnancy failure: a Scottish case–control study. Issue 1 (17th January 2022) - Wheelhouse, Nick; Kemp, Sadie; Halliday, Jo E B; Tingas, Efstathios Alexandros; Duncan, W Colin; Horne, Andrew W
Abstract : Lay summary: Q fever is a bacterial disease that passes between animals and humans and causes disease in both. The disease has been associated with pregnancy complications including miscarriage. This study was undertaken to identify if Q fever exposure was correlated with miscarriage in 369 women attending a pregnancy support unit in Edinburgh. The women in the study were in two groups, the miscarriage group with 251 women who had experienced a miscarriage and a control group of 118 women who had not experienced miscarriage. Three women were found to be positive for Q fever antibodies, suggesting that they had previously been exposed to the infection and all of them were from the group who had experienced miscarriage. The study indicates that Q fever is relatively rare in women attending an urban Scottish hospital suggesting that the infection is not a major cause of miscarriage in this population. However, as Q fever antibodies could only be found in women within the miscarriage group, it suggests that the infection cannot be ruled out as a potential cause of miscarriage in individual cases.